Utilizando experimento investigativo para ensinar ácidos e bases numa escola pública no município de Apuí - AM - Patrício, Juliana dos Santos (Brasil, 2024)
We know that Chemistry teaching needs constant updates due to advances that happen in society and how much they impact our daily lives. Therefore, teachers need to be aware of this reality and always seek training continued and constant, so that you can provide your students with a learning that contextualizes scientific knowledge with traditional knowledge. Thus,The present work aimed to use the experiment as a methodological resource by investigation to teach acids and bases to high school students (EM). This one The study was qualitative in nature and consisted of applying questionnaires before and after the carrying out experimentation to evaluate learning. The results of previous questionnaire revealed that students knew a little about the topics acids and acids bases and knew almost no examples. After the experimental activities, the students demonstrated greater knowledge, interest and motivation in the topics, proportion effectiveness in carrying out the practical activity. In the end, we concluded that the approach had an overwhelming result for teaching about chemical contents as well as whether showed a valuable strategy that can be used with other subjects and in other schools in the public education network.